FROM ALIENATION TO ACCEPTANCE: A MESSAGE FROM THE BUTTERFLY MOSQUE - M. Faqih Azam Majid; Defi Yulia Hardiana; Zulfi Zumala Dwi Andriani; M. Tazkiya syah (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
AbstractThis research aims to determine the form of Wilson's life journey in the novel